Design and fabrication of a chemical vapour deposition system with special reference to ZrC layer growth characteristics - Biira, S.; Crouse, P.L.; Bissett, H.; Hlatshwayo, T.T.; Laar, J.H. van; Malherbe, J.B. (Journal of the Southern African Institute of Mining and Metallurgy, 2017)
The overall aim of this research project was to design and construct an inhouse, thermal chemical vapour deposition (CVD) reactor system, operating at atmospheric pressure. Radio frequency (RF) induction heating was used as the energy source, with a vertical-flow design, using thermally stable materials. The steps in the design and construction of this CVD system are described in detail. The growth conditions at different substrate temperatures, gas flow ratios and substrate-gas inlet gaps were assessed as part of the project. The growth rate of ZrC layers increases with increasing substrate temperature. The microstructure properties of the ZrC layers such as lattice parameters and orientation of crystal planes were all found to be dependent on deposition temperature. The increase in free carbon in the as-deposited coatings as the temperature increased was found to be a stumbling block for obtaining stoichiometric ZrC coatings. The surface morphology of the as-deposited ZrC layers also depends on the deposition parameters.
Keywords: ZrC; Chemical vapour deposition; RF heating